A filosofia como mudança de morada [ΜΕΤΟΊΚΗΣΙΣ = METOÍKĒSIS] - Kussler, Leonardo Marques (Universidade do Vale do Rio dos Sinos, 2018)
The research now proposed deals with the possibility of retracing Philosophy to its original practices, which aimed not only at the theoretical development, but at the existential dialectic process, which was shown in the practical life of each philosopher, promoting Philosophy as a way of life. Thus, the main objective of this thesis is to explain the concept of experience from its Greek root, μετοίκησις [metoíkēsis], whose primary meaning is change of the abode [of being]. In tracing elements of the philosophical experience that combines philosophical discourse with the philosophical way of life, we begin an investigation of foreshadowing the aforementioned philosophical methodology in three dialogues of Plato, going through the renewal of the concept in the phenomenology of Hegelian idealism, and, finally, culminating in contemporary proposal of the Kyoto School, which, in our view, is a contemporary representative of this. The first chapter approaches philosophy from the metaphorical notion of the experience of death, based on the Platonic dialogues Apology, Crito and Phaedo. The relevance of reinterpreting and retranslating these texts in the possibility of renewing their understanding, either by the methodology used or by the establishment of a new hermeneutic paradigm, so that it is possible to avoid some interpretative paradigms that follow the Latin sub-titles of the Platonic dialogues. The second chapter, in turn, proposes a conceptual bridge of the Greek concept mentioned above to the concept of Erfahrung as it appears in Hegel’s Phenomenology of the Spirit. The proposal advocated here is that what is understood as the experience of consciousness described in the project of Hegelian phenomenology can be understood as a dialectical exercise of the subject that seeks to transform its way of being-in-the-world, as in the Greek proposal just mentioned. In addition to Hegel’s text, there are two main sections of Hegel’s first-instance commentators, mainly Heidegger and Gadamer, which corroborate our interpretative defense. The third chapter approaches the concept of μετανοεῖν [metanoeîn], resumed by the tradition of the Kyoto School from the perspective of philosophical experience, in which we propose a straight relation to the perspective developed in previous chapters. Here we show how Kitarō Nishida and Hajime Tanabe stand out as specialists in Hegel’s phenomenology and Heidegger’s ontology, which unite concepts of Japanese Buddhism and propose a form of Philosophy as a way of life, emphasizing the end of Philosophy as something that requires the existential commitment and the self-involvement of the philosopher.
Keywords: Metoíkēsis; Experiência filosófica; Platão; Hegel; Escola de Kyoto; Metoíkēsis; Philosophical experience; Plato; Hegel; Kyoto school; ACCNPQ::Ciências Humanas::Filosofia